For which cancers might patients benefit most from expedited symptomatic diagnosis? Construction of a ranking order by a modified Delphi technique. Issue 1 (December 2015) - Hamilton, Willie; Stapley, Sally; Campbell, Christine; Lyratzopoulos, Georgios; Rubin, Greg; Neal, Richard
Abstract Background This study aimed to answer the question 'for which cancers, in a symptomatic patient, does expediting the diagnosis provide an improvement in mortality and/or morbidity?' Methods An initial ranking was constructed from previous work identifying 'avoidable deaths' for 21 common cancers in the UK. In a two-round modified Delphi exercise, 22 experts, all experienced across multiple cancers, used an evidence pack summarising recent relevant publications and their own experience to adjust this ranking. Participants also answered on a Likert scale whether they anticipated mortality or morbidity benefits for each cancer from expedited diagnosis. Results Substantial changes in ranking occurred in the Delphi exercise. Finally, expedited diagnosis was judged to provide the greatest mortality benefit in breast cancer, uterine cancer and melanoma, and least in brain and pancreatic cancers. Three cancers, prostate, brain and pancreas, attracted a median answer of 'disagree' to whether they expected mortality benefits from expedited diagnosis of symptomatic cancer. Conclusions Our results can guide future research, with emphasis given to studying interventions to improve symptomatic diagnosis of those cancers ranked highly. In contrast, research efforts for cancers with the lowest rankings could be re-directed towards alternative avenues more likely to yield benefit, such as screening or treatment.